Determinan Kualitas Laporan Keuangan Puskesmas dengan Mediasi Pemanfaatan Teknologi Informasi - Sugiarti, Sri; Rahmatika, Dien Noviany; Akyuwen, Roberto; Setyowati, Ratna Faridah (Forum Kerjasama Pendidikan Tinggi, 2025)
Delays in reporting, errors in budget recording and calculation, and low compliance with Government Accounting Standards (GAS) reflect weak financial governance. This phenomenon demonstrates the complexity of problems in Community Health Center financial management that have the potential to affect public service accountability and public trust in health sector financial governance. This study aims to analyze the influence of internal control systems, financial literacy, and human resource competency on the quality of Community Health Center financial reports, with the use of information technology as a mediating variable. This study is motivated by the low quality of financial reporting in Community Health Centers in Brebes Regency, as indicated by late reporting, budget recording errors, and low compliance with Government Accounting Standards. This study uses a quantitative approach with a survey method of 196 respondents selected by cluster random sampling from 38 Community Health Centers. Data were analyzed using the Structural Equation Modeling (SEM) method based on Smart PLS. The results show that internal control systems, financial literacy, and human resource competency are three key variables that can improve the quality of financial reports in a directive manner. The internal control system showed the strongest impact (t = 2.454), followed by human resource competency (t = 2.850) and financial literacy (t = 2.845). All of these variables also contribute to increasing the adoption of information technology, with human resource competency providing the highest contribution (t = 5.399). Information technology itself has a significant influence on the quality of financial reports (t = 3.434). This finding has important implications for improving financial governance in the primary healthcare sector through strengthening human resource capacity, financial literacy, internal control systems, and digital transformation.